A Compact Inductive Position Sensor Made by Inkjet Printing Technology on a Flexible Substrate - Nataša Samardžić; Goran Stojanović; Dragana Vasiljević; Nikola Jeranče (Sensors, 2012)
This paper describes the design, simulation and fabrication of an inductive angular position sensor on a flexible substrate. The sensor is composed of meandering silver coils printed on a flexible substrate (Kapton film) using inkjet technology. The flexibility enables that after printing in the plane, the coils could be rolled and put inside each other. By changing the angular position of the internal coil (rotor) related to the external one (stator), the mutual inductance is changed and consequently the impedance. It is possible to determine the angular position from the measured real and imaginary part of the impedance, in our case in the frequency range from 1 MHz to 10 MHz. Experimental results were compared with simulation results obtained by in-house developed software tool, and very good agreement has been achieved. Thanks to the simple design and fabrication, smaller package space requirements and weight, the presented sensor represents a cost-effective alternative to the other sensors currently used in series production applications.